Proyek Internasional: Tantangan Abad 21 - Brigita Meylianti Sulungbudi (Center for Economic Studies Universitas Katolik Parahyangan, 2004)
The recent trend toward globalization, even in those countries which had opted to operate in isolation in the past, indicates that international projects will receive a greater thrust in the years ahead. This article identified benefits and threat of international project. We must do an environmental analysis or pre project country study to evaluate the feasibility of the international project in culture, geographical position , economic indicators, legal and political stability, business environment, and infrastructures.